The development and cultural foundations of dual apprenticeships : a comparison of Germany and Switzerland - Gonon, Philipp [Verfasser]; Deissinger, Thomas [Verfasser] (My University, 2021)
"Referring to historical debates and theories on vocational education and training (VET) since the 19th century and developments up to the present day, this paper considers the cultural conditions that were relevant for the emergence and legitimisation of vocational education and training and, in particular, the dual principle of apprenticeships in Germany and Switzerland. With reference to the theories of German Vocational Education Theory that emerged at the beginning of the 20th century and the concept of vocation (Beruf), i.e. the merging of occupation-based work and education, as it was propagated in particular by Georg Kerschensteiner, the development and establishment of dual vocational training in Germany and Switzerland is reconstructed, in line with what became the institutional framework of apprenticeships in the two countries. It is above all the focus on education in schools through Bildung as a pedagogical concept reaching beyond what may technically be associated with skill formation for jobs, but also the understanding that VET should be given a reliable institutional framework, that were crucial for the emergence and establishment of the modern VET system in both countries." (Author's abstract ; BIBB-Doku)
Keywords: S 1.3 Berufliche Erstausbildung; S System beruflicher Bildung; Berufspädagogik; I 2.1 Deutschland; I 2.2.1 Westeuropa; 370; Berufsausbildung; Berufsbildungssystem; Duales System; Berufspädagogik; Berufsbildendes Schulwesen; Bundesrepublik Deutschland; Schweiz